Multicystic dysplastic kidney disease at Chris Hani Baragwanath Academic Hospital ovevr a thirty year period - Lala, Nilesh (My University, 2017)
Introduction: Multicystic dysplastic kidney (MCDK) disease is a common non-inherited developmental anomaly, increasingly diagnosed antenatally. It is a single functional kidney associated with increased risk of anomaly of the opposite kidney. Methods: A retrospective descriptive study of paediatric patients with MCDK disease was undertaken at a secondary-tertiary level hospital from January 1986 to December 2015. Results: Over a 30 year period, 59 patients were identified; 36 (59%) were male and 31 (52.5%) were left sided. Overall, 20 (33.9%) of cases were diagnosed antenatally, with an increased frequency of cases diagnosed in the last decade (p=0.015). Eight (13.6%) had associated contralateral abnormalities; none had reflux into contralateral kidney. Conclusion: The number of MCDK diagnosed was low but increasing, due to increased antenatal sonars in the last decade. None of the patients had reflux into the contralateral kidney. The patients (only study from Africa) showed similar demographics to the rest of the studies on MCDK.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Paediatrics, Johannesburg 2017
Keywords: Multicystic Dysplastic Kidney